180k views
5 votes
Need help finding the factor of 2y^2-2y-4

User Kerb
by
5.0k points

2 Answers

3 votes

Answer:

2(y - 2)(y + 1)

Explanation:

Given

2y² - 2y - 4 ← factor out 2 from each term

= 2(y² - y - 2) ← factor the quadratic

Consider the factors of the constant term (- 2) which sum to give the coefficient of the y- term (- 1)

The factors are - 2 and + 1, since

- 2 × 1 = - 2 and - 2 + 1 = - 1 , then

y² - y - 2 = (y - 2)(y + 1)

Then

2y² - 2y - 4 = 2(y - 2)(y + 1) ← in factored form

User Ben Elgar
by
4.3k points
4 votes

Answer:

hope it helps you............

Need help finding the factor of 2y^2-2y-4-example-1
User Vitalii Vasylenko
by
4.7k points